The issue of active and passive smoking in a selected group of pregnant women - Trzaska, Małgorzata; Charzyńska-Gula, Marianna; Guźla, Natalia; Rutkowska, Eliza (Journal of Education, Health and Sport, 2018)
Nicotinism is one of the most common addictions found among pregnant women, with a substantial impact on the development of the foetus and the child’s upbringing. The addiction increases the risk of foetal disorders and death and many diseases in the infancy and childhood period. In order to analyse the issue of active and passive smoking in a selected group of pregnant women, a survey was carried out. The surveyed group consisted of 265 pregnant women staying at pregnancy pathology wards and primary healthcare centres in the Lubelskie Province. Surveys were carried out from October to December 2017. The diagnostic survey method with a proprietary community interview questionnaire were used. The survey demonstrated that around a half of pregnant women (51%) were active smokers. 80% of non-smoking respondents were exposed to passive smoking. A correlation was found between smoking during pregnancy, education and place of residence. The highest percentage of smoking women was found in the age group below 20 (75%) and pregnant women living in rural areas (61%). Among the smoking women, those with higher education were the least numerous. The obtained results point to the necessity of conducting studies on the issue of smoking among pregnant women and to the need of performing preventive measures to mitigate these problems.